A simple method for the detection of Leptolegnia chapmanii from infected Aedes Aegypti larvae - Leles, Renan N. (2013)
Significant progress in developing Leptolegnia chapmanii as a biological control agent against mosquitoes will be accelerated by improved and simpler methods to detect and to isolate this virulent and rapidly lethal watermold from fieldcollected mosquito larvae. To date, however, this oomycete has remained understudied and little used. This study presents a simplified method to detect Leptolegnia in infected Aedes aegypti larvae. The development of L. chapmanii inside mosquitoes is easily monitored when pathogen-treated larvae are quasi-immobilized for an initial 48 h in the water film on plates of water agar amended with antibiotic (chloramphenicol, 0.5–1 g/L) and fungicide (thiabendazole, 4–8 g/L) and then transferred to a larger volume of water for an additional 48 h. Surprisingly, chloramphenicol stimulated oosporogenesis by L. chapmanii. The method permits processing of large numbers of A. aegypti and other culicid larvae and is useful for both obtaining new strains and also monitoring the efficacy of L. chapmanii during field tests.